The impact of digital technology, social media, and artificial intelligence on cognitive functions: a review - Shanmugasundaram, Mathura; Tamilarasu, Arunkumar (Frontiers in Cognition, 2023)
In our modern society, digital devices, social media platforms, and artificial intelligence tools have become integral components of our daily lives, profoundly intertwined with our daily activities. These technologies have undoubtedly brought convenience, connectivity, and speed, making our lives easier and more efficient. However, their influence on our brain function and cognitive abilities cannot be ignored. This review aims to explore both the positive and negative impacts of these technologies on crucial cognitive functions, including attention, memory, addiction, novelty-seeking and perception, decision-making, and critical thinking, as well as learning abilities. The review also discusses the differential influence of digital technology across different age groups and the unique challenges and benefits experienced by children, adolescents, adults, and the elderly. Strategies to maximize the benefits of the digital world while mitigating its potential drawbacks are also discussed. This review aims to provide a comprehensive overview of the intricate relationship between humans and technology. It underscores the need for further research in this rapidly evolving field and the importance of informed decision-making regarding our digital engagement to support optimal cognitive function and well-being in the digital era.